Information System for Purchasing A Case Study Paper Mill - Athikulrat, kittichai (Srinakharinwirot University Engineering Journal, 2019)
The objective of this research is to improve the logistics process in case of the purchasing process in Craft Paper production. This research study Integrated Definition for function modeling (IDEF0) of purchasing department. The purchasing process is more complexed due to various procedures of data storages and many suppliers. This research proposes the use of a purchasing management software is needed in order to gain data accuracy and convenient to use for the purchasing staff. After trial use a purchasing management software, the result shows that the software be able to increase staff effectiveness and decreased complex processes. Previous average operating time was 200.98 minutes compared to current average operating time is 57.41 minutes, time decreased 71.43 percent. It concludes that a purchasing management software can reduce operating time and simplify purchasing process.